The Correlation of Occupational Stress with Guilt in the Nurses of Mofid Children\'s Hospital in Tehran, Iran - F Dolatshad; A Maher; SM Hosseini; A Aghili (Iran University of Medical Sciences, 2020)
Background & Aims: Occupational stress is inherent to all jobs, while it becomes more important in the jobs that involve humans. Evidence and studies suggest that the nursing profession is among the most stressful jobs. Considering the consequences of occupational stress on employeeschr('39') mental health, the feeling of mental health is widely affected by the perceptions of individuals toward events and occupational stressors. Stress diminishes attention, concentration, decision-making skills, and judgment and is also negatively correlated with the quality of care. In addition, stress leads to the increased incidence of mistakes and errors. Given the nature of the nursing profession, tendency to feeling the guilt of pathogen or diseases may adversely affect their health. In the occupations such as nursing in which the responsibility of the life and welfare of others is undertaken by nurses, guilt could be acute and significant, especially when several issues appear. However, few studies have been focused on the impact of guilt feelings on the wellbeing of nurses. Various studies have reported positive, significant correlations between guilt feelings and depression, anxiety, and stress. Therefore, the recognition and focus on solving the occupational issues of nursing staff as a great spectrum of healthcare providers are inherent to the national macro health planning. Stress, occupational stress, and their consequences on the physical, mental, and professional life of the nurses in healthcare organizations are among the issues that affect the goals and performance of these organizations. Therefore, obtaining more information about occupational stress, communications, and other related variables (e.g., guilt feelings) has attracted the attention of researchers. Materials & Methods: This descriptive, applied research was conducted in the summer of 2018 at Mofid Childrenchr('39')s Hospital in Tehran, Iran. The sample population consisted of all the employed nurses of the hospital (n=260), and 141 nurses were selected via simple random sampling using the name lists by drawing lots as the samples and enrolled in the study. No inclusion and exclusion criteria were defined for sample selection. After obtaining the required permit, explaining the research objectives to the subjects, and obtaining oral informed consent, the questionnaires were distributed and completed in the presence of the researcher. All the items of the questionnaires were completed by the participants without attrition. The data collection tool consisted of three sections, including the demographic characteristics of female nurses (ward of employment, education level, employment status, work shifts, age, marital status, and work experience), Osipow job stress questionnaire, and the caregiver guilt questionnaire (CGQ). Osipow job stress questionnaire has been developed to measure the stressors in the workplace (especially in hospital and healthcare settings) with 60 items and six dimensions, including heavy workload (professional role workload), incompetence (role dichotomy), incompatibility (role duality), role range, sense of responsibility, and physical problems. The items of the questionnaire were scored based on a five-point Likert scale. The total score of each female nurse was calculated within the range of 60-300 and classified into four levels of below the natural level, natural level, medium level, and severe level. The CGQ had five dimensions and 22 items regarding the feelings of guilt about the mistakes of the care receiver, challenges and failures of care, self-care, neglect of other relatives, and negative feelings toward others. The questionnaire items were scored based on a five-point Likert scale. The total score of each nurse was calculated by summing up the scores within the range of 22-110. The degree of guilt was categorized as low, moderate, and high. The internal consistency of the questionnaires was also confirmed, with the Cronbachchr('39')s alpha estimated at 89% and 88%, respectively. Data analysis was performed in SPSS version 16 using descriptive and inferential statistics. Results: Statistical analysis was performed on 141 returned, intact questionnaires. The mean age of the nurses was 33 ± 7.03 years, and their mean work experience was 7.56 ± 5.21 years. The mean score of guilt feelings was 3.93 ± 0.64, and the mean score of occupational stress was 4.29 ± 0.51. According to the findings, the majority of the nurses (69.5%) had severe stress and severe guilt feelings (55.4%). In addition, positive, significant correlations were observed between occupational stress and its dimensions with guilt feelings and its dimensions among the nurses (P<0.05). Conclusion: According to the results, occupational stress and guilt feelings were significantly correlated in the nurses, which could be due to work challenges, high stress of patient care, burnout, and guilt for the death of patients. The results of this study are consistent with the previous studies and theories regarding the impact of occupational stress on guilt feelings. Given the critical role of nursing staff in patients care and prevention of mortality, healthcare policymakers could take action to reduce the occupational stress of nurses by decreasing their working hours, eliminating continuous work shifts, increasing welfare services, and improving the conditions of the physical workplace. It is also suggested that nursing managers take measures considering factors such as the lack of emotional readiness, problems between colleagues, working schedules of nurses, and interactions with patients and their companions in order to reduce occupational stress and guilt feelings in nurses. Regarding the significant correlation between occupational stress and guilt, the application of job stress reduction techniques among the nurses of childrenchr('39')s hospitals is of paramount importance theoretically and operationally. Furthermore, the performance of nurses should be assessed in an environment with no stress and burnout, and the nurses with these issues must receive treatment immediately after they are identified, so that no harm would be done to their colleagues, family, and patients. The results of this study could be incorporated into nursing services (especially pediatric nursing) to attract the attention of the related authorities for awareness regarding the disruptive factors of mental health in nurses.